As "vítimas" de Rosa do Prado: Um estudo do direito penal sobre o MST no extremo sul da Bahia - Veloso, Marilia Lomanto (2006)
This Thesis aims to understand the meaning of victim from the analysis of the speech of the homeless country workers, on the daily fighting for the land, at Rosa do Prado Camp, southern of the state of Bahia, building an critical analysis of the speech of the penal system facing the land conflicts. On this direction it supposes that solving those events, the penal system takes place on ideological propositions about the idea of victim that allows to benefit the big owners and listening to the members of Landless Workers Movement (MST} could help to understand this meaning on the daily actions defending the land production. For that reason, the research has developed searching, from the beginning, the locus where the colonialism has put the indians, the colored people and the poor white people, (re)building the history of the social, political, economical juridical aspects, the main reasons of setting up the MST. Bringing to these days, on the context, the fights that took place as results of the social contradictions from the land system established by the Portuguese Court, that has been taking place today in Brazil. On the light of this hitorical study there is a responsibility of the system in the constitution of the no possessions person, consubstantiated on the condition of the incriminate landless victim. On the second study, preceded by a critical about the penal system and its ideological function on the exercise of social control, enphasis on campesino, the Thesis goes on victim analysis, of different instances throuh the human history theories about the meaning and kind of the incriminate homeless victim, that some say its the result of excluding economical social went from the landing of portuguese people in Brazil. The third study of Thesis and its meaning, it is the understanding of the speech from the people at Rosa do Prado Camp about the meaning of victim and the important kinds about the mattar. Their speechs bring expectations and critics about the intrigue of the formal and informal social control departaments about solving the problems of landless and MST showing the bureaucratic mecanism of the system (administrative, political, judicial) about the twelve years of waiting for solving the condition of the land people to set up projects with money from the government. On their speechs, the camp people have showed the life defense as a reason to justify their actions, voting the land reform as the only way to allow the social inclusion, that they have understood as a constitucional right. The understanding of the speechs of the camp people and their leaders, as individual persons (landless) or collectivized (MST) on the land fight, allows to say both resulting of the land system in the country, garanted by the ideological speech of the judicial system on the moment of solving the conflicts from the unsubmissible to the archetypal. The analysis of the speechs of the camp people dennying the incriminate to the owners of the land those mean incriminate homeless victims. This understanding should be considerated on the exam of judicial circunstances, not only at Rosa do Prado, but in all the instance that the system submits the landless and the MST to the penal and judicial consequences obliged by the same system that has built those victims